The corrosion potential of rock bolts on coal mines - Spearing, Sam; Mondal, K.; Bylapudi, G.; Weber, J.; Hirschi, J. (2011)
The US coal mining industry uses about 100 million rock anchors per year. Corrosion has been found to be an issue in Australian coal mines (Hebblewhite et al, 2003 and Villaescusa et al., 2007) where the problem has been well researched and stress corrosion has been found to be a significant cause of rock falls. Corrosion is also a major concern for underground civil construction in the US but has not been considered an issue or adequately researched in coal mines. Conditions are conducive to corrosion underground mainly because of water quality and humid conditions. There is a perception however that when bolts are fully grouted, adequate corrosion protection is offered to the steel. Research has shown that this is not necessarily the case due to the formation of micro-cracks as the resin sets and with subsequent rock movement shearing the resin column. The paper outlines a method to determine the corrosion potential of bolts used in long term excavations and suggests ways to mitigate such effects, based on research conducted in the lab and on three mines.